2021
DOI: 10.4314/sajas.v51i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Beta alanine effects immediately pre- and post hatch on chick quality, carcass yield and meat quality in broilers

Abstract: First, this study aimed to evaluate the effects on hatchability of in ovo supplementation of beta alanine (βA). Second, it assessed the effects on performance, meat quality and serum constituents of broiler chickens of βA injection in ovo and of supplementation with βA in feed for the first seven days after hatching. For this purpose, 960 fertilized broiler chicken eggs were distributed to hatchery trays in four treatment groups with six replicates on day 17 of incubation. The treatment groups consisted of egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Therefore, we examined reports on the in ovo injection of L-histidine and β-alanine. It has been reported that injecting β-alanine into the eggs can enhance hatching characteristics, carcass yield, and meat quality in broiler chickens ( Atan and Kop-Bozbay, 2021 ). Similarly, injecting L-histidine (0.55 mg) into the eggs on d 7 of incubation has been shown to improve hatchability, intestinal development, and growth performance ( Xu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we examined reports on the in ovo injection of L-histidine and β-alanine. It has been reported that injecting β-alanine into the eggs can enhance hatching characteristics, carcass yield, and meat quality in broiler chickens ( Atan and Kop-Bozbay, 2021 ). Similarly, injecting L-histidine (0.55 mg) into the eggs on d 7 of incubation has been shown to improve hatchability, intestinal development, and growth performance ( Xu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The decision on the timing of feeding of feed and useful feed additives also affects on chicken quality and yield ( Bhanja et al, 2010 ; Jha et al, 2019 ; Atan et al, 2021 ). Atan et al (2021) reported that period immediately before and after hatching is an important period that determines the efficiency and production of good quality chicken meat in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The decision on the timing of feeding of feed and useful feed additives also affects on chicken quality and yield ( Bhanja et al, 2010 ; Jha et al, 2019 ; Atan et al, 2021 ). Atan et al (2021) reported that period immediately before and after hatching is an important period that determines the efficiency and production of good quality chicken meat in broilers. Tavaniello et al (2020) found that in ovo injection of prebiotics (galactooligosaccharides) effective for alleviating HS mitigated the detrimental effects on meat quality in broilers in a high-temperature environment.…”
Section: Discussionmentioning
confidence: 99%
“…Before injection, two holes were made on the broad side of the eggs using 21 g needles to ease delivery of the extract and avoid tension in the eggs during delivery of the extract, the extract was injected using an automatic syringe, and thereafter, the holes were sealed with a adhesive tape. No group of eggs was injected with saline solution because previous studies ( Atan & Kop-Bozbay, 2021 ; Karamik & Kop-Bozbay, 2020 ), reported no significant difference between the saline-injected and non-injected eggs. All the injected eggs received 0.2 ml of the extract in the air space.…”
Section: Methodsmentioning
confidence: 99%